Anpassningarnas för(e)ställning - Om Skolinspektionens tillsyn som en scen för förändring - Judit Novak (Utbildning & Demokrati)
Scholars have studied various aspects of school inspection, examining its activities from different perspectives, but there is a lack of studies focusing on the perceptions and experiences of the inspectees. In Sweden, the Swedish Schools’ Inspectorate (SSI) has become a central tool for governing the education sector. On July 1, 2011, the new Education Act came into force and granted the SSI additional resources and powers to monitor and control schools. Drawing on social interaction theory, this article analyses interviews with head teachers, focusing on adjustments in rules and practices undertaken to meet the SSI’s compelling demands. The results show that head teachers mainly strived to adjust to formal requirements in the steering documents. In the case of complex deviations from the steering documents, teachers adjusted by changing the representation of the practice, not the practice itself, to fit the rule. A discussion is put forward about school inspections as a means of shaping a reality that is put on stage so that it can be acted upon, and how such inspections define a strategic landscape that practitioners must navigate.